Twelve Drummers Drumming… With Dystonia. Issue 1 (8th February 2021) - Bledsoe, Ian O.; Reich, Stephen G.; Frucht, Steven J.; Goldman, Jennifer G.
Background: Reports of drummers' dystonia are rare, particularly compared to the literature on dystonia in string, piano and brass players. Several cases of drummers' dystonia have been included in large series of multiple instrumentalists, but there are few reports comprised exclusively of drummers with musicians' dystonia. We present here a series of 12 drummers with task-specific, focal dystonia affecting their upper limbs while drumming and spanning multiple playing techniques and musical styles. Methods: We conducted a retrospective chart review of drummers with dystonia seen at academic Movement Disorders centers. Results: All 12 patients were male, and the majority eventually developed spread of dystonia to tasks other than drumming. Ten of the 12 had dystonia affecting their fingers, while 8/12 had dystonia affecting the wrist. Only 1/12 had involvement proximal to the wrist. Pharmacologic interventions were largely ineffective; 3 had some benefit from botulinum toxin injections, but this was limited by problematic weakness in one drummer. Discussion: The phenomenology in our series is concordant with prior reported cases, demonstrating frequent wrist involvement, though we also found that a greater proportion of patients had dystonia affecting the fingers. It could be hypothesized that different drumming techniques or musical styles modulate the relative risk of dystonic involvement of the different anatomical regions of the upper limb. Highlights: Drummers' dystonia is one of the least common forms of musicians' dystonia, though this may reflect fewer numbers of these instrumentalists. We present the largest series of drummers' dystonia and review previously published cases. Our cohort, representing diverse drumming styles, showed frequent involvement of dystonia in the wrists and fingers.